Understanding User Acceptance of AI-Enabled ERP Systems: A Preliminary Multi-Theory Conceptual Framework - Hajar MAIMOUNI; My Abdelouhab SALAHDDINE (Communications of International Proceedings, 2024)
The adoption and use of AI-Enabled ERP systems depends on a wide range of factors influencing user acceptance, including social, organizational, behavioral and technological aspects, among others. The motive of this study is to explore and analyze certain theoretical foundations that can provide an in-depth understanding of the key determinants of user behavior as to whether adopt or reject these new technologies. The literature gap highlights the potential for developing a framework that integrates diverse determinants to better understand user acceptance. To this end, we performed a general review of the theories covering the diverse aspects shaping the behaviors of users, and opted to focus our study on three theories, namely Unified Theory of Acceptance and Use of Technology 2, Diffusion of Innovations, and Perceived Value Theory. Subsequently, we developed an initial multi-theoretical framework aiming comprehension of user acceptance of AI-Enabled ERP systems. This framework sets the stage for a deeper effort to improve the comprehension and acceptance of such technologies by addressing key behavioral, social, and technological determinants.
Keywords: AI-Enabled ERP Systems; User Acceptance; Multi-Theory Framework; Technology Adoption